Bloomberg's folly. - FRENCH, HOWARD W. (Columbia Journalism Review)
The article discusses the foreign investigative reporting done into political corruption in China by journalists from news outlet "Bloomberg News." Topics discussed include the outlet's reporting on Chinese president Xi Jinping, a March 2014 speech by Bloomberg chairman Peter T. Grauer in which he claimed the Chinese investigative reporting got in the way of the company's efforts to sell computerized terminals with financial information, and reporting on Chinese politician Bo Xilai.